Uwarunkowania zewnętrzne a wyzwania dla narodowej polityki ekonomicznej Polski - Winiarski, Bolesław (External Conditions Versus Challenges for Polish National Economic Policy, 2008)
The article presents the autor's opinion on priorities of the long term economic policy in Poland. It gives reasons for the need for public discussion on the strategy for Polish economic policy in the context of complex external conditions, such as advancing globalization processes, demographic changes and their tendencies, increase of development and regional integration grouping consolidation. It also forms challenges and priorities for economic policy of the country, such as pro-family and pro-natal policy, regional policy, social, economic, and spatial cohesion; furthermore, it emphasizes the necessity for adjustment of the past policy of system reforms and their continuation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 13-28